Penerapan Media Pembelajaran Aplikasi Canva terhadap Kemampuan Menulis Aksara Sunda - Ira Rahmawati; Nunuy Nurjanah; Retty Isnendes (Prodi Pendidikan Bahasa dan Sastra Daerah, 2024)
This research aims to investigate the effectiveness of implementing technology-based learning media, especially the Canva application, in improving Sundanese writing skills. The research method used was an experiment with a pretest-posttest designone group. The sample for this research was class X students at a high school in Kuningan. The experimental group received learning using the Canva application. Data was collected through a Sundanese writing test before and after the intervention. The results of data analysis showed a significant increase in the ability to write Sundanese script in the experimental group. These findings confirm that the application of the Canva application learning media can be effective in improving the writing skills of Sundanese script in high school students. The pedagogical implications of this research support the integration of technology in regional language learning to improve students' skills in writing Sundanese script.